The morphology of integrated self-assembled monolayers and their impact on devices – A computational and experimental approach - Novak, Michael; Jäger, Christof; Rumpel, Armin; Kropp, Henning; Peukert, Wolfgang; Clark, Timothy; Halik, Marcus (Organic Electronics, 2010)
We report on a combined experimental and computational study on self-assembled monolayers (SAMs). The dielectric properties of SAMs based on n-alkyl phosphonic acids in large area thin film devices (organic field-effect transistors with good hole mobilities up to 0.3 cm² V−1 s−1 at −1 V and capacitors) depend on their chain length, but not consistently to theoretical pictures of tunneling through saturated n-alkanes. An unexpected saturation of current density with increasing chain length was obtained in devices, what impact on the leakage current in transistors and current density in capacitors. This is attributed to different self-assembled monolayer morphology ranging from an amorphous state for short alkyl chains to a quasi-crystalline state for longer alkyl chains. Molecular dynamics (MD) simulations provide a deeper insight into the nature of the three-dimensional intermolecular interactions and support the proposed SAM morphology. The change in morphology leads to a reduced effective SAM thickness in devices, which could be described by a Simmons approach quantitatively. The morphological aspect of self-assembled molecules is of enormous importance beyond the applications of SAMs in low-voltage, high mobility organic transistors because of it’s relevance for the hole field of molecular scale electronics. It demonstrates that even small changes in the molecular design can change the molecular interactions and monolayer assembly.